Immunogenicity and safety of a tetanus-diphtheria vaccine and a 13-valent pneumococcal conjugate vaccine after concomitant vaccination in ≥ 50-year-old adults - Joon Young Song; Hee Jin Cheong; Ji Yun Noh; Min Joo Choi; Jin Gu Yoon; Saem Na Lee; Seong Hui Kang; Eun Joo Jeong; Yu Mi Jo; Woo Joo Kim (BMC Infectious Diseases, 2018)
Abstract Background When two or more vaccines are administered concurrently, there is concern about safety and immunogenicity from vaccine interaction. Methods Subjects aged ≥50 years were randomized 1:1:1 to receive tetanus-diphtheria (Td) + 13-valent pneumococcal conjugate vaccine (PCV13; Group 1), PCV13 alone (Group 2), or Td alone (Group 3). After single or concomitant vaccination, enzyme-linked immunosorbent assay and opsonophagocytic assay (OPA) were performed to compare immunogenicity for Td and PCV13, respectively. Results A total of 448 subjects were available for the assessment. After concomitant administration, the non-inferiority criteria of geometric mean titer (GMT) ratios were met for tetanus, diphtheria, and all four pneumococcal serotypes (1, 5, 18C, and 19A). However, subjects in Group 3 (Td alone) were more likely to have a high IgG anti-tetanus antibody titer (≥ 0.5 U/mL) than those in Group 1 (Td + PCV13) (p <  0.01). As for the pneumococcal serotype 1, the OPA GMT was significantly higher in Group 1 (PCV13 + Td) compared to Group 2 (PCV13 alone) (p = 0.02). No serious adverse event occurred. Conclusions Concomitant Td and PCV13 administration induced sufficient immunity without significant interference and showed good safety profiles. Trials registration NCT03552445 registered at http://www.clinicaltrials.gov on June 11, 2018 (retrospectively registered).